Borders and Mobility in South Asia and Beyond - Jones, Reece; Ferdoush, Md Azmeary; Jones, Reece; Ferdoush, Md Azmeary (Amsterdam Amsterdam University Press, 2018)
The world is experiencing one of the largest movements of people in history with 65 million people displaced by conflict in 2015, the majority of which were from Asia. This book brings a deep engagement with individuals whose lives are shaped by encounters with borders by telling the stories of a poor Bangladeshi women who regularly crosses the India border to visit family, of Muslims from India living in Gulf countries for work, and the harrowing journey of a young Afghan man as he sets off on foot to Germany. The international and interdisciplinary work in this book contributes to this moment by analyzing how borders are experienced by migrants and borderlanders in South Asia, how mobility and diaspora are engaged in literature and media, and how the lives of migrants are transformed during their journey to new homes in South Asia, the Middle East, North America, and Europe.
English
Keywords: Society & culture: general; Migration, immigration & emigration; Borders, Mobility, South Asia, Diaspora, Migration